MANAGEMENT OF PATIENTS WITH BREAST PATHOLOGY ACCORDING TO BI-RADS CLASSIFICATION - Zhumaeva D.R. (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Resume. To make a correct diagnosis, it is necessary to have diagnostic criteria that make it possible to accurately prescribe treatment. Modern requirements for diagnostic methods are accuracy, high information content, and accessibility. The article discusses the BI-RADS (Breast Imaging Reporting and Data System) international system for describing and processing mammography and ultrasound data, which has been gaining interest in our country in recent years. The BI-RADS system is a good tool for determining the algorithm of management of patients with breast diseases.